Gingival zenith and its role in redefining esthetics: A clinical study - Babita Pawar; Pratishtha Mishra; Parmeet Banga; P P Marawar (Wolters Kluwer Medknow Publications, 2011)
Background: The purpose of this study was to quantify some clinical parameters useful as esthetic guidelines when gingival contour is modified and to compare the left and right sides of six maxillary anterior teeth. Materials and Methods: Maxillary casts mounted on an articulator according to the axis orbital plane were photographed from 35 young adults. The angle formed between the gingival line and maxillary midline (GLA) and the distance between the gingival zenith of the lateral incisor and the gingival line were measured (LID) using a flexible protractor and digital vernier caliper, respectively. The asymmetry was evaluated using a paired t test for the left vs right measurements of GLA and LID. The descriptive statistics for GLA and LID were calculated. Results: The GLA measurements of the left side (86.7΀΁4.2΀) were significantly greater than those of the right side (84.6΀΁5.4΀), and the mean absolute symmetry for GLA was 1.7΀΁4.4΀. The mean LID measurement was 0.92΁0.11. Conclusions: The gingival zenith of the canine is apical to the gingival zenith of the incisors (GLA <90΀) and the gingival zenith of the lateral incisor is below or on (17%) the gingival line when head is oriented on the axis orbital plane. A directional asymmetry was shown with the right side higher than the left side. Along with the other parameters related to dental esthetics, these clinical parameters may serve as esthetic guidelines and may enable us to obtain a more predictable outcome.